(untitled) (International journal of artificial intelligence, 2026)
The article analyzes the stages of development of Uzbek visual art during the 1960s–1980s, particularly the issues of searching for national identity, the dialectics of tradition and innovation, and the interaction between Eastern and Western aesthetic systems. The influence of ethnocultural dominants on artistic plastic language is examined through the works of such artists as N. Kashina, Ch. Akhmarov, R. Akhmedov, J. Umarbekov, and B. Jalolov. In addition, a comparative analysis with Kazakh, Turkmen, Tajik, and Kyrgyz schools reveals the common tendencies and distinctive features of Central Asian artists.